Microangiopathy is Common in Submucosal Vessels of the Colon in Patients With Diabetes Mellitus (The Review of Diabetic Studies, 2023)
OBJECTIVES: The pathophysiology behind gastrointestinal dysmotility in diabetes mellitus is unknown. Both esophageal dysmotility and gastroparesis have been shown to be associated with retinopathy, suggesting that microangiopathy is important in the common etiology. The aim of the present study was to examine whether patients with diabetes exhibit microangiopathy in the colon, and if present, to correlate microangiopathy with the clinical picture. METHODS: Consecutive patients subjected to colon surgery were identified in the southernmost districts of Skåne between January 2011 and May 2013. Medical records were scrutinized, and patients with a history of diabetes were noted. Gender, age, type of diabetes, treatment, complications, and other concomitant diseases were registered. Histopathologic reevaluation of surgical biopsies with morphometric analyses of submucosal vessels in the colon was performed. Morphometric examination and clinical data were compared with non-diabetic patients. RESULTS: Of 1135 identified patients during the time period studied, 95 patients with diabetes were recognized and included. Fifty-three non-diabetic, randomly chosen patients served as controls. The mean age was 71.8 ± 10.2 and 71.4 ± 9.5 years in diabetic and nondiabetic patients, respectively. Microangiopathy was found in 68.4% of diabetic patients and in 7.5% of non-diabetic patients (p < 0.001). The wall-to-lumen ratio was 0.31 (0.23- 0.46) in patients with diabetes compared with 0.16 (0.12- 0.21) in non-diabetic patients (p < 0.001). No clinical association with microangiopathy could be verified. CONCLUSION: Microangiopathy in the colon is more common in diabetic than in non-diabetic patients. The clinical significance of microangopathy has yet to be clarified.